Efeito da terapia de fotobiomodulação em modelo in vitro de adenocarcinoma pulmonar - Hironaka, Juliana Ricci Paes de Barros (2022)
Introduction: Cancer is an abnormal cell growth that invades neighboring tissues. Pulmonary adenocarcinoma is a type of lung cancer, classified as non-small cell carcinoma (NSCLS).In 2020, lung cancer recorded an incidence of 19 million cases worldwide. In Brazil, INCA (National Cancer Institute) pointed out 30,000 new cases with 29,000 deaths from the disease. this type of cancer is directly linked to tobacco consumption. The diagnosis is made through complementary exams: chest X-ray, bronchoscopy, among others. The treatment is surgical, but most cases are diagnosed in advanced stages, for this reason the search for new therapies has been growing. An example is therapy with low-level laser (LLLT). Objective: To evaluate the dosimetry and the effects of photobiomodulation in an in vitro model of urethane-induced lung adenocarcinoma. To quantify chemical mediators (IL-6, IL-8, IL-10, (IL-1β and IFN- ) and functional activity of BEAS induced by urethane and irradiated by LLLT with two energy densities (3J and 7.5J). Materials and methods: BEAS-2B cell line, cultured in RPMI(?) 1640+ fetal bovine serum 100 U/ml 1% glutamine gentamicin After 24 hrs cells were incubated with urethane (375g/ml). 1 hour of incubation were or not irradiated with LLLT (#J or 7.5J) at 660 nm. After 24 hrs the supernatant was collected for dosing. Cultures were separated into 4 groups: Medium (cells only); LLLT (irradiated cells irradiated with LLLT), urethane (cells stimulated with urethane), Urethane+LLLT (cells stimulated with urethane and irradiated with LLLT) Results: We observed an increase in the release of IL-1β, IL-6 and IL-8 and a reduction of IL-10 in the urethane group in relation to the medium group. On the other hand, we found a reduction in IL-1 β, IL-6 and IL-8 and an increase in IL-10 and IFN- in the urethane+LLLT group in relation to the urethane group. Conclusion: Photobiomodulation showed favorable effects both in irradiation with 3J and 7.5J but with different mechanisms, with the energy intensity of 3 J showing the best effect on urethane-induced BEAS cells. New in vivo studies should complement our findings to prove this promising effect of photobiomodulation.